High Rate of Transfer of Staphylococcus aureus from Parental Skin to Infant Gut Flora - Lindberg, Erika (American Society for Microbiology, 2004)
Many Swedish infants carry Staphylococcus aureus in their intestinal microflora. The source of this colonization was investigated in 50 families. Infantile S. aureus strains were isolated from rectal swabs and stool samples at 3 days and at 1, 2, 4, and 8 weeks of age. The strains were identified by using the random amplified polymorphic DNA method and compared to strains from swab cultures of the mothers' hands, nipples, and nares and from the fathers' hands and nares. Maternal stool samples were also obtained at a later stage to compare infant and adult intestinal S. aureus colonization. Although 60% of 1-month-old children had S. aureus in the stools, this was true of only 24% of the mothers. The median population numbers in colonized individuals also differed: 10(6.8) CFU/g of feces among infants at 2 weeks of age versus 10(3.2) CFU/g of feces in the mothers. Of S. aureus strains in the stools of 3-day-old infants, 90% were identical to a parental skin strain. A total of 96% of infants whose parents were S. aureus skin carriers had S. aureus in their feces and 91% had the same strain as at least one of the parents. In comparison, only 37% of infants to S. aureus-negative parents had S. aureus in the stool samples. Thus, infantile intestinal S. aureus colonization was strongly associated with parental skin S. aureus carriage (P = 0.0001). These results suggest that S. aureus on parental skin establish readily in the infantile gut, perhaps due to poor competition from other gut bacteria.